A PESTEL Analysis of Problems Associated with the Adoption of Offsite Construction: A Systematic Literature Review - Kola Olayiwola; Srinath Perera; Mike Kagioglou; Xiaohua Jin; Pejman Sharafi (Buildings, 2025)
Offsite construction (OSC) is fragmented and involves a complex network of stakeholders in all the stages such as planning, design, legal approval, site preparation, modular manufacturing, transportation, storage, and onsite installation. The barriers include complexity of the process; lack of awareness; supply chain challenges in capacity and knowledge; cultural perception; lack of viable business process models or solutions; scarcity of skills in design/manufacturing/construction and lack of government regulations and legislation. This study, therefore, categorises the barriers according to political, economic, social, technological, environmental, and legal (PESTEL) analysis. The PESTEL analysis aims at providing organisations a comprehensive list of all the external barriers against the adoption of offsite construction. A wholistic list of all the barriers and understanding the barriers will help them to improve the overall productivity and contribute to the economy metrics. Utilising popular databases, including Scopus, Web of Science, and Google Scholar, a systematic literature review of 56 papers relevant to OSC adoptions in the construction industry research was conducted. From the review, the barriers to the adoption of OSC in the construction research and relevant organisations reports were identified. The research shows that countries such as Australia, UK, China, Hong Kong, Singapore, and New Zealand have been the top countries in which papers on OSC were published. A relationship analysis shows that political barriers amounting to 5 out of the 101 barriers identified having the most causal effects on the low adoption of OSC.